Investigation of the role of the endofungal bacterium Rhizobium radiobacter in the tripartite Sebacinalean symbiosis - Guo, Huijuan; Justus Liebig University Giessen (My University, 2016)
Endofungal bacteria as symbionts residing in the fungal mycelium and spores were first describes as Bacteria-Like Organisms (BLOs) in 1970 s (Mosse 1970). The bipartite relationship between fungi and terrestrial plants on the rhizosphere becomes complicated tripartite interaction as the discovery of endobacteria. In the last decade, research focussed on the endobacteria in arbuscular mycorrhizal fungi (Bonfante and Anca 2009; Naumann et al. 2010; Salvioli et al. 2015), in ectomycorrhizal basidiomycete fungus (Bertaux et al. 2005), and in rice pathogenic fungus Rhizopus microsporus (Partida-Martinez and Hartweck 2005; Moebius et al. 2014). We extended the former work to explore and establish a model tripartite symbiosis system among the Sebacinalean fungus Piriformospora indica, the Alphaproteobacterium Rhizobium radiobacter and a broad spectrum of plants. The free-living bacterial strain R. radiobacter F4 (RrF4) showed similar colonization pattern as its fungal host P. indica in plant roots. RrF4 cells heavily colonizedthe root maturation zone, embedded in dense polysaccharides biofilms and were interwoven in cellulose fiber-like structures on the root surface. Thereafter, RrF4 cells entered into inner tissue through lateral root emergence, root hair protrusion and cracks on the root, proliferated in the intercellular space in the rhizodermal and cortical layers into the central vascular system. Nevertheless, RrF4 only invaded and colonized the dead root cells instead of inducing plant host cell death. The systemic resistance mediated by RrF4 is based on the jasmonate-based ISR pathway, and defense gene expression resembles that observed with P. indica (Gleaser et al. 2015). The increased amount of endobacteria R. radiobacter in plant roots inoculated with P. indica, and the significantly reduced amount of endobateria in the sub-cultured P. indica that was isolated from plant roots indicate endobacteria R. radiobacter obtain more benefit from the tripartite relationship with both fungal and plant hosts than in the bipartite relation with only the fungus. It is an open question whether the endobacteria R. radiobacter released from P. indica into root tissue during the fungal colonization on plant. It was not successful to cure P. indica from the endobacteria through antibiotics treatment and single protoplast cultivation. However, we obtained a P. indica culture with reduced amount of endobacteria R. radiobacter, and partially cured P. indica showed low beneficial activity on plants. We presume the endobacteria R. radidobacter inside P. indica are at a stationary phase, which is the reason for the low number, small size and resistance to antibiotics in axenic culture. The endobacteria R. radiobacter resuscitate from stationary phase to growth phase when there is third partner plant supplying with enough nutrition and better propagation conditions, which results in the increased amount of endobacteria R. radiobacter when P. indica colonized on plant root. Taken together, this study underlines the crucial role of endofungal bacteria in the tripartite symbiosis. Further studies are needed to better understand the mechanism of R. radiobacter in the tripartite interaction, such as the regulation of mRNA on transcriptome level.

Endofungale Bakterien wurden als Symbionten, die im pilzlichen Myzel residieren, zuerst in den 1970ern als Bakterien-ähnliche Bacteria-Like Organisms (BLOs) beschrieben (Mosse 1970). Mit der Entdeckung von Endobakterien ist aus der zweiteilige Symbiose von Pilzen und terrestrischen Pflanzen eine komplizierten dreiteiligen Symbiose geworden. Im letzten Jahrzehnt konzentrierte sich die Forschung auf Endobakterien in Arbuskulären Mykorrhizapilze (Bonfante and Anca 2009; Naumann et al. 2010; Salvioli et al. 2015), in ektomykorrhizalen Basidiomyceten (Bertaux et al. 2005) und in den Reispflanzen befallenden Rhizopus microspores (Partida-Martinez and Hartweck 2005; Moebius et al. 2014). Bei Sharma et al. (2008) wurde erstemals gezeigt, dass auch der endophytische Sebacinaleen Pilz Piriformospora indica Wirt eines Endobakteriums ist. Dieses wurde als Rhizobium radiobacter (syn. Agrobacterium tumefaciens) identifiziert und konnte in Reinkultur kultiviert werden (Stamm R. radiobacter F4, RrF4). In der vorliegenden Studie wurde die bisherige Arbeit zu dieser dreiteiligen Symbiose zwischen P. indica, dem Alphaproteobakterium Rhizobium radiobacter und einem breitem Spektrum von Pflanzen näher untersucht. Zusammenfassend betont diese Studie die entscheidende Rolle der endofungalen Bakterien in der dreiteiligen Symbiose von P. indica, dem Endobakterium und den entsprechenden Wirtspflanzen. Weitere Untersuchungen sind erforderlich, um ein tieferes Verständnis der Rolle von RrF4 in der dreiteiligen Beziehung zu erhalten, wie zum Beispiel die Regulierung der Gen Expression auf Transkriptionsebene.
Keywords: symbiosis; endofungal bacteria; Sebacinalean; ddc:630